Pengembangan Dimensi Psychological Well-Being Untuk Pengurangan Risiko Gangguan Depresi - Primalita Putri Distina; Muhammad Husein Kumail (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Depression has become one of the most common psychological disorders and causes health and disability problems worldwide. Many cases of suicide are caused by depression disorder. In Indonesia, the prevalence of depressive disorder is relatively high and occurs in all age ranges. Many factors cause depression disorder; one of them is stress. Stress which is not managed properly can cause several problems such as, low moods, feelings of irritability, sleep disturbances, and changes in cognitive abilities such as reduced concentration. These symptoms can be one of the risk factors for depression. One approach in psychology related to mental health problems is positive psychology. Psychological well-being is a construct of positive psychology that is often used as a form of intervention that focuses on human development. Based on some research results, psychological well-being related to a mental health problem, including depression. The dimensions in psychological well-being are self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth also have a positive role in mental health. By developing the dimensions of psychological well-being in life, it can be a way to reduce the risk of depression.